Securitization, Transparency, and Liquidity - Pagano, Marco; Volpin, Paolo (Review of Financial Studies, 2012)
We present a model in which issuers of asset-backed securities choose to release coarse information to enhance the liquidity of their primary market, at the cost of reducing secondary market liquidity. The degree of transparency is inefficiently low if the social value of secondary market liquidity exceeds its private value. We show that various types of public intervention (mandatory transparency standards, provision of liquidity to distressed banks, or secondary market price support) have quite different welfare implications. Finally, we extend the model by endogenizing the private and social value of liquidity and the proportion of sophisticated investors. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com ., Oxford University Press.